Llamas, Barter and Travel Rituals: An Ethnographic Study on the Esquela Tusuy Dance of the Uchumiri Peasant Community, Condesuyos, Peru - Aleixandre Brian Duche-Pérez; Lolo Juan Mamani-Daza (Religions, 2024)
The “Esquela Tusuy” dance is a cultural manifestation deeply rooted in the Uchumiri Peasant Community (Condesuyos, Peru), reflecting the intersection between traditional cultural practices and community identity. This ethnographic study reveals how the dance, beyond being a mere artistic expression, is a complex system of meanings that articulates social relations, economic practices of barter, and Andean spirituality, through the veneration of Pachamama and Apu Coropuna. The dance is organized around rituals that include the preparation, journey, and return of the llama herders, being a living expression of collective memory and a mechanism of social cohesion. The adopted methodology was based on participant observation and semi-structured interviews, allowing a detailed understanding of Uchumiri’s cultural dynamics. Despite contemporary challenges, “Esquela Tusuy” remains a central pillar for the affirmation of cultural identity and community resistance, underlining the importance of dance in the conservation of cultural heritage and in the articulation of local identities against national narratives.